2014
DOI: 10.3406/bspf.2014.14435
|View full text |Cite
|
Sign up to set email alerts
|

Lingots et déchets de fonderie dans les dépôts de l’horizon de l’épée à pointe en langue de carpe (Bronze final IIIb) ; proposition de typologie

Abstract: Les lingots de cuivre et les déchets de fonderie sont des objets omniprésents dans les dépôts métalliques terrestres de l'horizon de l'épée à pointe en langue de carpe du Bronze final IIIb (Bronze final atlantique 3), en particulier dans les régions proches de la façade atlantique. Et pourtant, ils ont été systématiquement sous-étudiés et même sousréférencés. Après un passage en revue des différentes descriptions de ces objets depuis un siècle, ce travail propose une typologie fine basée sur leurs descriptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Large plano-convex ingots are present in the greatest number in northwestern France (Brittany) (Boulud and Fily, 2009;Le Carlier de Veslud et al, 2014), and have a morphology similar to examples found in England (Wang et al, 2018). On the other hand, the small ingot is the most prevalent type found on the Iberian Peninsula (Montero Ruiz et al, 2011;Ramos, 1993).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Large plano-convex ingots are present in the greatest number in northwestern France (Brittany) (Boulud and Fily, 2009;Le Carlier de Veslud et al, 2014), and have a morphology similar to examples found in England (Wang et al, 2018). On the other hand, the small ingot is the most prevalent type found on the Iberian Peninsula (Montero Ruiz et al, 2011;Ramos, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…Today, the marks are preserved only in photographs from the excavation field reports (Garcia 2002:39). Following the general convention of most authors (e.g., Boulud and Fily, 2009;Le Carlier de Veslud et al, 2014;Montero Ruiz et al, 2011;Ramos, 1993), LBA-EIA plano-convex ingots can be distinguished based on size (weight): small ingots, weighing up to 2 kg, and large ones, weighing more than 2 kg (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…Most, if not all, these ingot fragments are of plano-convex type, which are a frequent inclusion in late Ewart Park hoards from south-eastern England and western France (Le Carlier de Veslud et al . 2013, 509–10).…”
Section: Objects Within Hoardsmentioning
confidence: 99%
“…Ve střední Evropě vznikla již řada tematicky vyhraněných děl o kovových slitcích. Problematice se věnovaly obecnější studie (Mozsolics 1981;Primas -Pernicka 1998;Bachmann et al 2003;Modl 2010;Nessel 2014;Möslein 2015;Skolaut 2017) či metodické práce (Czajlik 1996;Le Carlier de Veslud -Edme -Fily 2014;Modl 2019). Výzkum se zaměřoval na metriku koláčovitých ingotů (Rusu 1981;Skolaut 2017) či na rozsáhlejší série materiálových analýz (Rychner -Kläntschi 1995;Höglinger 1996;Tram pužOrel 1996;Bachmann et al 2003;Sperber 2004;Pernicka -Mehofer 2013;Lutz -Krutter -Pernicka 2019;Möslein -Pernicka 2019).…”
Section: Východiska Poznáníunclassified